New Multi-Locus Sequence Typing of Mycoplasma hyorhinis Isolated from Pig Farms in Central Thailand - P. Fungwithaya; S. Samngamnim; S. Luengyosluechakul; P. Assavacheep (Tropical Animal Science Journal, 2022)
Mycoplasma hyorhinis (M. hyorhinis) is an important pathogen in the pig industry, especially during the nursery period. Multi-locus sequence typing (MLST) is a specific method used to identify many bacterial species. At present, 108 MLST schemes of M. hyorhinis have been reported around the world. This study aimed to investigate the variable multi-locus sequence typing (MLST) schemes of M. hyorhinis in pig herds from bacterial stock at the large animal hospital, Faculty of Veterinary Science, Chulalongkorn University, since 2010. Bacteria were collected from 98 deceased pigs sent for autopsy at this veterinary hospital. Samples were collected from at least one lesion per pig located in the joint capsule, lung, thoracic cavity, abdominal cavity, and pericardium. Bacteria were cultured and confirmed the species by PCR. MLST was detected by PCR and DNA sequencing. Sequence data were reported to GenBank and PubMLST databases. In this study, the positive results of M. hyorhinis were found on 75 samples, while 23 samples gave negative results. The highest population of this pathogen was shown on the joint organ but no significant difference with the other organs. Only nine positive samples could be cultured, purified, and sent for sequencing. Sequencing results revealed 6 MLST schemes, while 5 of them were defined as new ST types (ST71-75) defined for the first time in Thailand. A diverse array of MLST in this location, some of which are novel, implied that bacteria might adapt to their environment. MLST information might play a role in vaccine development and preventative strategies.